A comprehensive urban floodplain dataset for model benchmarking. Issue 3 (2nd July 2016) - Smith, Grantley Paul; Rahman, Priom Faria; Wasko, Conrad
ABSTRACT: Floodplain managers require accurate and reliable information quantifying flood flow behaviour to support effective land-use planning and flood emergency planning. Two-dimensional numerical models, typically solving the shallow water approximation of the Navier–Stokes equations, have become a de-facto standard for predicting design flow behaviour. In urban floodplains, the built environment can have a profound influence on the passage and distribution of floodwaters. Obstacles such as buildings, fences and walls can block and redistribute flows overriding the gradient of the topography and locally increasing the flood hazard. The development and application of numerical models for urban floodplains is open to considerable interpretation and numerous modelling techniques have been proposed to represent the buildings and other obstacles to flow. Here, a comprehensive dataset for an urban overland flow path is developed to help practitioners assess numerical model performance. A physical model of the Morgan–Selwyn floodway in Merewether, Newcastle, Australia was developed and validated against the historical extreme June 2007 'Pasha Bulker' storm. Detailed measurements of the flow behaviour were then collected. The comprehensive dataset of the physical model topography, flood flow boundary conditions as well as detailed measurements of flow depth and velocity are freely available to practitioners who wish to further investigate the dataset or apply the dataset in their numerical modelling.